Design and and analysis of platform motorcycle dynamometer - Mohd Hanif, Mokhtar (2008)
The performance of a motorcycle usually measured by the producing of horsepower, HP and torque force, TQ, due to maximum revolution of tire per minute, RPM. In order to measure the HP and TQ of a motorcycle, the motorcycle dynamometer is very suitable and efficient. This machine is quite new and latest technology in Malaysia and still not be used wisely by the Malaysian until today because lack of knowledge and technology of development of a motorcycle dynamometer. Thus, there is a needed to study and understand the technology used behind the development of a motorcycle to increase the use of it at any automotives laboratories or workshops in Malaysia. This study was done in order to design and analysis of platform motorcycle dynamometer due to the capability of machines and materials available in Faculty of Mechanical Laboratory. In this study, the reverse engineering was used to design the machine by review the available motorcycle dynamometer which already exists and produced by various manufacturers around the world. Then, design of a tough platform motorcycle dynamometer which can support load and able to absorb the vibrations was produced. To design and analysis this platform and its inertia roller, the CAD software and CAE software were used to design and illustrate the structure. Lastly, as the results, the design analysis with different materials of structure was done to illustrate the stress von Mises.